Perubahan Digital dalam Pencitraan Bangsa selama Krisis: Tinjauan Sistematis atas Strategi Komunikasi Ukraina dalam Perang Rusia-Ukraina - Reztrianti, Diajeng; Usep Suhud; Mohamad Rizan (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
Since February 2022, the Russia-Ukraine war has intensified the urgency of nation branding, positioning digital marketing communication as a crucial tool for building and maintaining national brand equity. This study aims to systematically map strategies, key variables, and the outcomes achieved through digital marketing communication in Ukraine’s nation branding during wartime. Employing a PRISMA-based systematic literature review (SLR) of 42 Scopus-indexed articles published between 2022 and 2025, the study finds that the orchestration of digital communication via social media, online campaigns, and multichannel diplomacy is essential in constructing narratives of solidarity, public trust, and Ukraine’s global reputation. The main findings reveal strong collaboration among the state, local governments, diaspora, and global actors who leverage various platforms such as Twitter/X, TikTok, websites, crowdfunding, memes, and cloud services to disseminate national narratives, foster audience engagement, and manage public opinion in real time. The study further highlights a shift in nation branding strategies from conventional diplomacy to a digital-first approach, where success is driven by message consistency, technological adaptation, and multi-actor collaboration. This research contributes a conceptual framework for digital nation branding and offers practical recommendations for governments and digital communication practitioners seeking to build national image in times of conflict.